MAKING DINOSAUR NAMES USING APHYXOIDS OF GREEK AND LATIN ORIGIN - Самойленко, Олена (SWorldJournal, 2025)
The article is devoted to the functioning of term elements of Greek and Latin origin in the biological field. As illustrative material, the names of dinosaurs are used, for the creation of which the suffixoid -завр is the most productive. Prefixoids are